EFFECTS OF ULTRASOUND ON THE MORPHOLOGY, PARTICLE SIZE, CRYSTALLINITY, AND CRYSTALLITE SIZE OF CELLULOSE - SUMARI SUMARI; ACHMAD ROESYADI; SUMARNO SUMARNO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of this study is to optimize ultrasound treatment to produce fragment of cellulose that is low in particles size, crystallite size, and crystallinity. Slurry of 1 % (w/v) the cellulose was sonicated at different time periods and temperatures. An ultrasonic reactor was operated at 300 Watts and 28 kHz to cut down the polymer into smaller particles. We proved that ultrasound damages and fragments the cellulose particles into shorter fibers. The fiber lengths were reduced from in the range of 80-120 µm to 30-50 µm due to an hour ultrasonication and became 20-30 µm after 5 hours. It was also found some signs of erosion on the surface and stringy. The acoustic cavitation also generated a decrease in particle size, crystallinity, and crystallite size of the cellulose along with increasing sonication time but it did not change d-spacing. However, the highest reduction of particle size, crystallite size, and crystallinity of the cellulose occurred within the first hour of ultrasonication, after which the efficiency was decreased. The particle diameter, crystallite size, and crystallinity were decreased from 19.88 µm to 15.96 µm, 5.81 Å to 2.98 Å, and 77.7% to 73.9% respectively due to an hour ultrasound treatment at 40 °C. The treatment that was conducted at 40 °C or 60 °C did not give a different effect significantly. Cellulose with a smaller particle and crystallite size as well as a more amorphous shape is preferred for further study.